Pengelolaan Pemeliharaan Infrastruktur Sanitasi Program Pamsimas di Kecamatan Pekalongan Utara - Sintha Ayu Cahyaningtyas; Mardwi Rahdriawan (Jurusan Perencanaan Wilayah dan Kota, 2016)
Infrastructure development especially in the field of sanitation in Indonesia is stilllagging behind other countries in Southeast Asia. One of the efforts undertaken by theIndonesian government to improve the quality of sanitation infrastructure is through WaterSupply and Sanitation for Low-Income Communities (WSSLIC). WSSLIC is a community-basedprograms that involve the community in any implementation activities. Besides, theimplementation of the WSSLIC program in each region which beneficiariesalso based oninitiative of the community itself.Sanitation issues commonly found in many settlements incoastal areas. Pekalongan, especially in the District of North Pekalongan in particular is one ofthe coastal areas are still struggling with the problem of sanitation. Six villages in the District ofNorth Pekalongan has received WSSLIC program, but the effort to manage the maintenance ofsanitation infrastructure program by community is not the same between each village, thoughstill within the scope of the same area. This study aims to determine how the management isdone in the respective village communities in the District of North Pekalongan so it can be thecause of the decline of quality of sanitation and the things that hinder the successfulcommunity management.The approach used in this study is a qualitative approach using descriptive methods in analysistechniques. Sampling object and subject of research is done by using purposive sampling.Samples research objects taken six samples, one sample from each village and coded samplesA-F. There is three stages of analysis in this study, first is the identification of physical changessanitary building in each village; second is maintenance management analysis carried out bythe people in each village that includes planning program by community, entity formationmanagers, program implementation, and monitoring; and third is to do a comparison betweenthe findings of the study with community managed water and sanitations program in India.Based on the analysis, in this study showed that community efforts in the management andmaintenance of sanitation infrastructure in the form of public toilets is strongly influenced bythe level of awareness and public participation as users. There are also other factors that alsoinfluence the successful management of the maintenance of sanitation infrastructure ofWSSLIC program by the people in the District of North Pekalongan namely environmentalconditions, catastrophic flooding, socio-economic conditions of society, the level of usersdemand, the relationship between the community and the government, and there absence ofsupervision by the government as a provider of program.